I am plastic : the designer toy explosion - Budnitz, Paul (New York : Abrams, 2006)
Beginning with urban vinyl artists, the phenomenon has taken root not only in the toy world but also in the global art community. This work presents a survey of the vinyl toy craze that began in Hong Kong in 1996 and quickly spread across the Far East to Europe and the United States.
1. Introduction -- 2. Japan -- 3. China -- 4. Europe -- 5. United states -- 6. Elsewhere -- 7. Interviews -- 8. Acknowledgments -- 9. Index
Keywords: Plastic toys